(untitled) (Prithvi Academic Journal, 2023)
The Government of Nepal (GoN) has approved the Malaria Strategic Plan with the aim of ’Malaria free Nepal by 2025’. This study aimed to determine the factors associated with the mosquito bed nets and its determinants of the ownership with reference to the households’ wealth status in Nepal. The study used the secondary data from the Nepal Demographic and Health Survey 2016. The households’ characteristics were considered independent variables and ownership of the mosquito nets as the dependent variable. We used IBM SPSS Statistics 22 to analyse the data. The data showed that three fourths of the total households had such nets, where 80 percent were urban households as compared to 68 percent rural households, 95 percent from the Terai region of Nepal as compared to 34 percent from the mountain region, 91 percent were of middle income, as compared to 39 percent the poorest wealth status of households, 84 percent of households that had TV as compared to 66 percent of the households with no TV used the nets. The poorest households were 52 percent less likely to own the nets as compared to the richest households (a OR = 0.48, 95% CI: 0.39-0.60, p<0.001). The wealth status of households, residence setting in terms of urban or rural area, and eco-belt migration history of the households, and households having radio and TV were significant predictors for the nets ownership. Special attention was paid by the government and policymakers to the poorest families, rural households, households in the mountain region of Nepal, and households having no radio and TV to meet the national target of the government plan with the use of public health promotion planning and intervention.